Glifosato na disponibilidade do manganês em solos - Taffarel, Teane (2020)
Transgenic production has expanded worldwide. Consequently agricultural inputs consumption also, with emphasis on the herbicide glyphosate. As an industrial chelator, glyphosate can form tridentate complexes with cations due to three functional groups of its structure: phosphate, amino and carboxylate. After glyphosate application, transgenic soy can show physiological symptoms, known as “yellow flashing”. Theories claim that this herbicide can form complexes with manganese (Mn) and iron (Fe) or change the soil microbiota preventing the use of these nutrients by soy. Glyphosate can reach soil through direct application or after the straw decomposition. Use of isotherms facilitates to understand interaction between molecules and soil particles. Few studies elucidate interaction of glyphosate with Mn directly in soils, that’s why this study was proposed. Thus, the objective was to evaluate the sorption of Mn in two soils of contrasting textures under different doses of glyphosate. For this, batch methodology was used, with the following concentrations of MnSO4 0; 15.8; 27.8; 43.2 and 57.1 mg L-1 . While glyphosate doses were 0; 2.5; 12.5; 50 and 125 L ha-1 . All solutions were prepared with calcium chloride (CaCl2) 0.01 mol L-1 . After reading the concentrations pH was measured. Freundlich isotherm was better adapted to data obtained, thus, the constants Kf and N were calculated. Statistic used was in a completely randomized design (CRD), with three replications, and analysis of variance for Kf, N and the sorbed element (X/m). When significant, Scott Knott test at 5% probability was used. Although no statistical difference was found between Freundlich isotherm coefficients (Kf and N), X/m showed more intensive sorption at the highest doses of glyphosate and Mn associations, therefore, it is not indicated to exceed recommended technical doses. The pH decreased with increasing doses, demonstrating that ion concentration takes priority over pH.